Comparing epidemiologically estimated treatment need with treatment provided in two dental schemes in Ireland - Guiney Helena; Felicia Patrick; Whelton Helen; Woods Noel (BMC, 2012)
Abstract Background Valid estimation of dental treatment needed at population level is important for service planning. In many instances, planning is informed by survey data, which provide epidemiologically estimated need from the dental fieldworkers' perspective. The aim of this paper is to determine the validity of this type of information for planning. A comparison of normative (epidemiologically estimated) need for selected treatments, as measured on a randomly-selected representative sample, is compared with treatment actually provided in the population from which the sample was drawn. Methods This paper compares dental treatment need-estimates, from a national survey, with treatment provided within two choice-of-dentist schemes: Scheme 1, a co-payment scheme for employed adults, and Scheme 2, a 'free' service for less-well-off adults. Epidemiologically estimated need for extractions, restorations, advanced restorations and denture treatments was recorded for a nationally representative sample in 2000/02. Treatments provided to employed and less-well-off adults were retrieved from the claims databases for both schemes. We used the chi-square test to compare proportions, and the student's t-test to compare means between the survey and claims databases. Results Among employed adults, the proportion of 35-44-year-olds whose teeth had restorations was greater than estimated as needed in the survey (55.7% vs. 36.7%;p <0.0001). Mean number of teeth extracted was less than estimated as needed among 35-44 and 65+ year-olds. Among less-well-off adults, the proportion of 16-24-year-olds who had teeth extracted was greater than estimated as needed in the survey (27.4% vs. 7.9%;p <0.0001). Mean number of restorations provided was greater than estimated as needed in the survey for 16-24-year-olds (3.0 vs. 0.9; p <0.0001) and 35-44-year-olds (2.7 vs. 1.4;p <0.01). Conclusions Significant differences were found between epidemiologically estimated need and treatment provided for selected treatments, which may be accounted for by measurement differences. The gap between epidemiologically estimated need and treatment provided seems to be greatest for less-well-off adults.